2007
DOI: 10.1128/jb.00513-07
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Oligomerization of the F Conjugative Coupling Protein TraD

Abstract: Type IV secretory systems are a group of bacterial transporters responsible for the transport of proteins and nucleic acids directly into recipient cells. Such systems play key roles in the virulence of some pathogenic organisms and in conjugation-mediated horizontal gene transfer. Many type IV systems require conserved "coupling proteins," transmembrane polypeptides that are critical for transporting secreted substrates across the cytoplasmic membrane of the bacterium. In vitro evidence suggests that the func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…Thus, in addition to the N-terminal region, the C-terminal segment and the NBD region of TrwB were involved in TrwB-TrwB interactions. Similar results were obtained with the T4CPs TraD of the F plasmid and TcpA of plasmid pCW3: the TMD is important for oligomerization, together with another segment of the cytoplasmic domain (23,50). It was suggested that the N-terminal domain of TraD is required for the interaction of the T4CP with the rest of the conjugal machinery, while the region of the soluble domain would only be required for self-interactions.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Thus, in addition to the N-terminal region, the C-terminal segment and the NBD region of TrwB were involved in TrwB-TrwB interactions. Similar results were obtained with the T4CPs TraD of the F plasmid and TcpA of plasmid pCW3: the TMD is important for oligomerization, together with another segment of the cytoplasmic domain (23,50). It was suggested that the N-terminal domain of TraD is required for the interaction of the T4CP with the rest of the conjugal machinery, while the region of the soluble domain would only be required for self-interactions.…”
Section: Discussionsupporting
confidence: 70%
“…The cytoplasmic domain of the related TraD protein of plasmid R1 stimulates both transesterase and helicase activities of its cognate relaxase, TraI (41,51). A series of random mutations were shown to affect TraD oligomerization (23). In VirD4, the T4CP of the VirB T4SS of A. tumefaciens, both the periplasmic domain plus key residues of the NBD are required for its location at the cell poles (31); its interaction with the T4SS protein substrate VirE2 does not require the N-terminal TMD (2).…”
mentioning
confidence: 99%
“…In support of the latter hypothesis, the presence of the membrane-spanning domain altered interactions of native TrwB with some ligands in vitro (31). Moreover, Traxler and colleagues have shown that associations between F plasmid TraD monomers in vivo require N-terminal transmembrane sequences and that formation of stable, higher-order TraD oligomers in the inner membrane also appeared to involve other F proteins (28). Accordingly, the model of Fig.…”
Section: Discussionmentioning
confidence: 58%
“…TraD stimulates DNA cleavage at nic in combination with full-length TraI via mechanisms not supported by the isolated transesterase domain (41). TraD requires an additional F plasmid protein(s) to form stable multimers in the membrane (23). We propose that TraD is not yet assembled in the hexameric form required for ATP hydrolysis (58,59).…”
Section: Discussionmentioning
confidence: 99%